Site-selective probe of magnetic excitations in rare-earth nickelates using resonant inelastic X-ray scattering - Lu, Yi; Haverkort, Maurits W. (Physical review. X, Expanding access, 2018)
We use high-resolution resonant inelastic x-ray scattering (RIXS) to study a thin film of NdNiO3, a compound whose unusual spin- and bond-ordered electronic ground state has been of long-standing interest. Below the magnetic ordering temperature, we observe well-defined collective magnon excitations along different high-symmetry directions in momentum space. The magnetic spectra depend strongly on the incident photon energy, which we attribute to RIXS coupling to different local electronic configurations of the expanded and compressed NiO6 octahedra in the bond-ordered state. Both the noncollinear magnetic ground state and the observed site-dependent magnon excitations are well described by a model that assumes strong competition between the antiferromagnetic superexchange and ferromagnetic double-exchange interactions. Our study provides direct insight into the magnetic dynamics and exchange interactions of the rare-earth nickelates and demonstrates that RIXS can serve as a site-selective probe of magnetism in these and other materials.